STRATEGI PEMASARAN PADA DIVISI MARKETING DI BUILD BETTER COMMUNICATION (BBC) ENGLISH TRAINING SPECIALISTCILEGON - Zulkarnain, Rizal (Universitas Banten Jaya, 2021)
The main goal of a company that takes profit and this can also be a measure of the success or failure of a company in receiving. In addition, effectiveness and efficiency in running the company also plays an important role. The efficiency in question is a marketing strategy that is carried out with the right considerations and considerations so that there is no waste of costs both in operational and in advertising promotion costs and the effectiveness referred to in selecting the right marketing strategy in accordance with the market served by the company so that the targets set can be reached.